PCK1 activates oncogenic autophagy via down-regulation Serine phosphorylation of UBAP2L and antagonizes colorectal cancer growth - Xiangyan Zhang; Geru Tao; Jie Jiang; Tingting Qu; Shuchao Zhao; Ping Xu; Ya’nan Zhao; Xiaoming Xing; Shucun Qin (Cancer Cell International, 2023)
Abstract Phosphoenolpyruvate carboxykinase 1 (PCK1) is the rate-limiting enzyme in gluconeogenesis. PCK1 is considered an anti-oncogene in several human cancers. In this study, we aimed to determine the functions of PCK1 in colorectal cancer (CRC). PCK1 expression in CRC tissues was tested by western blot and immunohistochemistry analyses and associations of PCK1 level with clinicopathological characteristics and disease survival evaluated. Further, we studied the effect of PCK1 on CRC cell proliferation and the underlying mechanisms. Our results show that PCK1 is expressed at significantly lower levels in CRC than in control tissues. High PCK1 expression was correlated with smaller tumor diameter and less bowel wall invasion (T stage). Overexpression and knockdown experiments demonstrated that PCK1 inhibits CRC cell growth both in vitro and in vivo. Mechanistically, PCK1 antagonizes CRC growth via inactivating UBAP2L phosphorylation at serine 454 and enhancing autophagy. Overall, our findings reveal a novel molecular mechanism involving PCK1 and autophagy, and highlight PCK1 as a promising candidate therapeutic target in CRC.